The story of math - Du Sautoy, Marcus; McGann, Karen; Dashwood, Robin; Berry, David; Duke, Kim.; British Broadcasting Corporation; Open University; Athena (Firm); Acorn Media (Firm) (Silver Spring, MD : Athena : Distributed exclusively by Acorn Media U.S., 2009)
In this landmark series of films, University of Oxford Professor Marcus du Sautoy escorts viewers through the history of this most important of all intellectual disciplines. In a journey that takes him through the ages and around the world, he examines the development of key mathematical ideas and shows how, in a multitude of surprising ways, mathematical ideas underpin the science, technology, and culture that shape our world.
Bonus material: The music of the primes (78 min.) -- Mathematician biographies.
Subtitled for the deaf and hard of hearing.
Title from container.
Presented by Marcus du Sautoy.
Originally produced as episodes of the television mini-series: The story of maths.
Program content: c2008.
DVD; NTSC; 16x9 widescreen; Dolby digital stereo.
Keywords: Mathematics -- History; Documentary television programs; Nonfiction television programs